2016
DOI: 10.1155/2016/4670672
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation Boot Camp: A Simulation-Based Pilot Study

Abstract: Objectives. Management of mechanically ventilated patients may pose a challenge to novice residents, many of which may not have received formal dedicated critical care instruction prior to starting their residency training. There is a paucity of data regarding simulation and mechanical ventilation training in the medical education literature. The purpose of this study was to develop a curriculum to educate first-year residents on addressing and troubleshooting ventilator alarms. Methods. Prospective evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
0
25
0
2
Order By: Relevance
“…One obvious application, and the primary purpose of this study, is to provide the basis of simulationbased medical education and research, particularly in the art and science of mechanical ventilation. 62 Simulationbased medical education and simulation-based mastery learning have become well-established in undergraduate and graduate medical, nursing, and allied health-care training programs. 63 Much like a standardized patient, 64 a highfidelity lung simulator can provide the framework for teaching virtually any aspect of the physical interaction of a patient and a mechanical ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…One obvious application, and the primary purpose of this study, is to provide the basis of simulationbased medical education and research, particularly in the art and science of mechanical ventilation. 62 Simulationbased medical education and simulation-based mastery learning have become well-established in undergraduate and graduate medical, nursing, and allied health-care training programs. 63 Much like a standardized patient, 64 a highfidelity lung simulator can provide the framework for teaching virtually any aspect of the physical interaction of a patient and a mechanical ventilator.…”
Section: Discussionmentioning
confidence: 99%
“… 20 This is probably due, in part, to the fact that instruction in MV is not well standardized, because there is no widely used list of competencies in MV, nor is there consensus on how to develop a specific curriculum in MV and to quantify learning. 18 , 24 , 27 - 29 …”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in the mean total score after the rotation shows a significant gain of knowledge after the training focused on MV management, a gain that was also observed in a study involving residents who underwent intensive training in MV. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yee et al reported that a 12-hour simulation-based mechanical ventilation boot camp significantly improved the confidence, knowledge and performance of first-year residents in the management of the ventilated patient 12. Similarly, Spadaro et al have demonstrated improved knowledge and skills of anaesthesia residents who were taught acute respiratory distress syndrome (ARDS) management with manikin-based simulation, in contrast to computer-based simulation.…”
Section: Introductionmentioning
confidence: 99%